Assessment and Diagnosis barriers for Students with Communication Disorders from the Prospective of Speech Specialists in Al-Madinah Al-Munawwarah - Toukhi, Shatha Sabir; Alharbi, Ghadah Ghazi (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify assessment and diagnosis barriers for students with communication disorders from the prospectives of speech specialists in Madinah. To achieve the objectives of the study, a questionnaire was designed consisting of (32) items distributed in (4) sections (physical barriers, barriers related to standards, administrative barriers, and Human barriers) which were answered by (109) of the speech specialists in the special education centers and programs in Madinah. The results showed that the level of barriers in assessment and diagnosing students with *communication disorders* from the point of view of speech specialists in Madinah was to a large degree, where the physical barriers section was in the first place, and in the second place came the administrative barriers, followed by the barriers related to standards in the third place, and in the fourth and last place came the human barriers, there were no statistically significant differences at the level of Significance (α≤0.05) for the responses of speech specialists in estimating the barriers to assessment and diagnosing students with communication disorders in Madinah according to the gender variable (males and females), and to the educational qualification variable (bachelor and postgraduate studies), and in-service vocational training variable (with training, no training). While it was found that there were statistically significant differences at the significance level (α≤0.5) for the responses of speech specialists in estimating administrative barriers to assessing and diagnosing students with communication disorders in Medina according to the gender variable in favor of females.